Why Margaret Still Matters - Sterling-Golden, Martha (Maine Policy Review, 2010)
In this commentary, Martha Sterling-Goldman reflects on the complexities of women in public life, and why it is important to prepare women to fully engage in political life. She says we must train a generation of women and men who think about power in a different way.
Keywords: women in public office; women and leadership